2016
DOI: 10.15517/am.v27i2.24359
|View full text |Cite
|
Sign up to set email alerts
|

Carbono orgánico del suelo en bosques riparios, arrozales y pasturas en Piedras, Tolima, Colombia.

Abstract: <p class="p1">El objetivo del estudio fue estimar el almacenamiento de carbono orgánico del suelo (COS) en la interface entre bosques riparios y una matriz de arrozales y pasturas con manejo orgánico. La investigación se efectuó en el municipio de Piedras, Departamento del Tolima, Colombia. Se seleccionaron dos lotes en producción (arroz y pastura) y se estimó el COS en ellos y en borde e interior de bosques riparios adyacentes a 0-20 cm de profundidad. Se cuantificó la densidad aparente y la concentraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
4
0
3
Order By: Relevance
“…Values found in the study are coherent with the reports by Andrade-Castañeda et al (2016) report 47.5Mg C/ha, a value similar to the results of this current study. Tree density in the systems studied by Arce et al (2008) was of 676 trees/ha, with the highest number for shade individuals, which is consistent with the results on this study in Co+S, where it was found that it stored 50.6Mg C/ha.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Values found in the study are coherent with the reports by Andrade-Castañeda et al (2016) report 47.5Mg C/ha, a value similar to the results of this current study. Tree density in the systems studied by Arce et al (2008) was of 676 trees/ha, with the highest number for shade individuals, which is consistent with the results on this study in Co+S, where it was found that it stored 50.6Mg C/ha.…”
Section: Resultssupporting
confidence: 93%
“…This physical variable of soils turned out similar among the HSPS, AFS+plantain, and C systems (1.33-1.35g/cm 3 ), while Co+S, LSPS, and BF showed a BD between 1.40 and 1.43g/ cm 3 (Figure 2). This tendency was also evinced in the findings of Andrade-Castañeda et al (2016), who found values of BD for riparian forests, riparian forest margins, and agricultural matrix (rice, pastures), of 1.7, 1.1, and 1.0g/cm 3 , respectively. This contrasts with the findings of Andrade et al (2018), where no BD differences in agriculture and riparian forests were detected in the basin of Combeima river (Ibagué, Colombia).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Another important factor in understanding soil ES in terms of nutrient provision, via organic matter and Frontiers in Environmental Science frontiersin.org productivity, is the community of soil organisms, since they directly impact cultivation yields and indirectly via nutrient cycles -food chains and modification of the soil structure (Barrios, 2007). In the Orotoy basin, Morinelly (2016), reported the Acarí class and the Entomobryidae, Formicidae and Termitidae families, as the most abundant, while the highest values of indices of richness, abundance, diversity and dominance were the ESPs tropical humid forest (gallery forest) of the lower zone and for the fairness index the highest value was from the grassland ESPs (open). Thus, it is possible to highlight the functional importance of biological communities in the soil and in turn, the role of the soil in the The ES provision of soil nutrients is related to biodiversity, the capacity to capture, retain and transport water or carbon, and is largely determined by the capacity of each soil to form and decompose organic matter (Victoria et al, 2012), as established in each ESPU.…”
Section: Discussionmentioning
confidence: 99%
“…Estos valores son próximos a los reportados por Andrade-Castañeda et al (2016) quienes obtuvieron una densidad aparente ente 1,1 y 1,7 g/cm 3 .…”
Section: Especies Arbóreas Representativasunclassified